Tau protein squired by molecular chaperones during alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Journal of Molecular Neuroscience, 2018)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive neuronal loss, caused by misfolding and accumulation of tau and Amyloid -42. Cellular mechanisms involving phosphatases, chaperones, ubiquitin proteasome system (UPS) and aggresomes solubilize or remove these toxic aggregates. Chaperones such as Hsp70 and Hsp90 functions in folding tau to its native form or in the downstream degrade and eliminated tau from the cell. Chaperones are involved in lysosomal degradation of tau by a process called chaperone mediated autophagy (CMA). In pathological conditions, chaperones fail to remove the toxic tau species, leading to their accumulation. In this scenario, inhibiting the chaperone activity would aid in overcoming AD. Small molecules inhibitors against chaperone activity are known to be effective in the clearance of aberrant tau from cell. In this review, the aspects of inhibition and prevention of tau aggregates formation are discussed in terms of chaperone activity and their small molecule modulators.

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Tau aggregates improve the Purinergic receptor P2Y12-associated podosome rearrangements in microglial cells - Chinnathambi, Subashchandrabose; Das, Rashmi; Desale, Smita Eknath (Biochimica Et Biophysica Acta-Molecular Cell Research, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that is associated with protein misfolding, plaque accumulation, neuronal dysfunction, synaptic loss, and cognitive decline. The pathological cascade of AD includes the intracellular Tau hyperphosphorylation and its subsequent aggregation, extracellular Amyloid-& beta; plaque formation and microglia-mediated neuroinflammation. The extracellular release of aggregated Tau is sensed by surveilling microglia through the involvement of various cell surface receptors. Among all, purinergic P2Y12R signaling is involved in microglial chemotaxis towards the damaged neurons. Microglial migration is highly linked with membrane-associated actin remodeling leading to the phagocytosis of extracellular Tau species. Here, we studied the formation of various actin structures such as podosome, lamellipodia and filopodia, in response to extracellular Tau monomers and aggregates. Microglial podosomes are colocalized with actin nucleator protein WASP, Arp2 and TKS5 adaptor protein during Tau-mediated migration. Moreover, the P2Y12 receptors were associated with F-actin-rich podosome structures, which signify the potential of Tau aggregates in microglial chemotaxis through the involvement of actin remodeling.
Keywords: Alzheimer `s disease; Filopodia; microglia; Podosome; Tau aggregates

TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization: a specialized Tau perspective - Kapoor, Mahima; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2023)
Microtubule-associated protein, Tau has been implicated in Alzheimer's disease for its detachment from microtubules and formation of insoluble intracellular aggregates within the neurons. Recent findings have suggested the expulsion of Tau seeds in the extracellular domain and their prion-like propagation between neurons. Transforming Growth Factor-beta 1 (TGF-beta 1) is a ubiquitously occurring cytokine reported to carry out immunomodulation and neuroprotection in the brain. TGF-beta-mediated regulation occurs at the level of neuronal survival and differentiation, glial activation (astrocyte and microglia), amyloid production-distribution-clearance and neurofibrillary tangle formation, all of which contributes to Alzheimer's pathophysiology. Its role in the reorganization of cytoskeletal architecture and remodelling of extracellular matrix to facilitate cellular migration has been well-documented. Microglia are the resident immune sentinels of the brain responsible for surveying the local microenvironment, migrating towards the beacon of pertinent damage and phagocytosing the cellular debris or patho-protein deposits at the site of insult. Channelizing microglia to target extracellular Tau could be a good strategy to combat the prion-like transmission and seeding problem in Alzheimer's disease. The current review focuses on reaffirming the role of TGF-beta 1 signalling in Alzheimer's pathology and cytoskeletal reorganization and considers utilizing the approach of TGF-beta-triggered microglia-mediated targeting of extracellular patho-protein, Tau, as a possible potential strategy to combat Alzheimer's disease.
Keywords: Alzheimer's disease; Cytoskeleton reorganization; Extracellular Tau; microglia; TGF-beta; TGF-beta 1